Co-expression of YieF and PhoN in Deinococcus radiodurans R1 improves uranium bioprecipitation by reducing chromium interference. (November 2018) - Xu, Rong; Wu, Kejia; Han, Huawen; Ling, Zhenmin; Chen, Zhengjun; Liu, Pu; xiong, Jian; Tian, Fake; Zafar, Yusuf; Malik, Kamaran; Li, Xiangkai
Abstract: Overexpression of the enzyme phosphatase (PhoN/PhoK) in the radiation-resistant bacterium Deinococcus radiodurans could be an efficient strategy for uranium remediation. However, the presence of other metals in nuclear wastes often interferes with uranium bioprecipitation. In our study, the uranium-precipitating ability of the PhoN-expressing D. radiodurans strain ( Deino-phoN ) significantly decreased by 45.4% in 13 h in the presence of chromium (VI); however, it was partially recovered after supplementation with chromium (III). Therefore, the reduction of chromium (VI) to chromium (III) was obtained by the co-expression of the YieF protein and PhoN in D. radiodurans ( Deino - phoN - yieF ). As a result, an increase in the chromium (VI) reduction (25.1%) rate was observed in 24 h. Furthermore, uranium precipitation also increased by 28.0%. For the decontamination of groundwater, we immobilized Deino - phoN - yieF cells using Polyvinyl alcohol (PVA)-sodium alginate (SA) beads, followed by incubation in a bioreactor. Approximately 99% of chromium (VI) and uranium (VI) was removed after 4 continuous cycles operated for a period of over 20 days at room temperature (25 °C). Therefore, Deino - phoN - yieF could be used as a potential biological agent for mixed radioactive nuclear waste remediation. Graphical abstract: Image 1 Highlights: Microbial U(VI) bioprecipitation is inhibited by Cr(VI). Co-expression of YieF and PhoN in Deinococcus enhances Cr(VI) reduction. Co-expression of YieF and PhoN accelerates U(VI) precipitation. Immobilized Deino-phoN-yieF is a promising remediation agent in nuclear waste.